2021
DOI: 10.1371/journal.pone.0258786
|View full text |Cite
|
Sign up to set email alerts
|

Radiological correlates of vocal fold bowing as markers of Parkinson’s disease progression: A cross-sectional study utilizing dynamic laryngeal CT

Abstract: Objective To determine whether arytenoid cartilage position and dynamics change with advancing duration and severity (as graded by MDS-UPDRS part III scores) in Parkinson’s disease, in a cross-sectional study design, we performed laryngeal four-dimensional computed tomography (4D-CT) in people with Parkinson’s disease and controls. Methods 31 people with Parkinson’s disease covering a range of disease duration and severity and 19 controls underwent laryngeal 4D-CT whilst repeatedly vocalizing. We measured on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 23 publications
0
14
0
4
Order By: Relevance
“…We hypothesized that a repetitive vocalization task with laryngeal 4D-CT could reveal differences in arytenoid cartilage movements between pwPD and healthy control participants. In our prior work [ 11 , 12 ], two key measurements were taken which were 1) the minimum distance between the arytenoid cartilages (denoted the inter-arytenoid distance or IAD), and 2) the glottic area. We previously demonstrated that changes to arytenoid cartilage posturing distinguish pwPD from healthy controls.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We hypothesized that a repetitive vocalization task with laryngeal 4D-CT could reveal differences in arytenoid cartilage movements between pwPD and healthy control participants. In our prior work [ 11 , 12 ], two key measurements were taken which were 1) the minimum distance between the arytenoid cartilages (denoted the inter-arytenoid distance or IAD), and 2) the glottic area. We previously demonstrated that changes to arytenoid cartilage posturing distinguish pwPD from healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that changes to arytenoid cartilage posturing distinguish pwPD from healthy controls. pwPD have a reduction in the IAD and an increase in the glottic area during vocalization [ 11 , 12 ]. We also found that as the condition advances over both time and clinical severity, the IAD progressively decreases while the glottic area increases [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations